The Effectiveness of Pregnancy Exercise and Birthing Ball Use on Labor Progress among Pregnant Women - Gita Rahmadani; Tutik Rahayu; Hernandia Distinarista (Health Gate, 2026)
Physical unpreparedness, manifestations of anxiety, and pain intensity often hinder labor progress, which in turn escalates the risk of invasive medical interventions. Non-pharmacological approaches, particularly through prenatal exercise activities and the use of birthing balls, are considered to have a positive contribution in optimizing labor mechanisms. This study aims to investigate the efficacy of prenatal exercise and birthing ball education on parameters of smooth labor processes in mothers. The methodology applied was a quasi-experimental design with a pretest-posttest control group design approach. A total of 62 respondents were involved as samples distributed into the experimental group and the control group. The intervention group received treatment in the form of prenatal exercise and education on the use of birthing balls, while the control group only received standard midwifery care. Data were collected through observations using standardized instruments, which were then analyzed using the Mann-Whitney U statistical test. The analysis results showed a significant difference in the level of smooth labor between the intervention and control groups. Pregnant women who received prenatal exercise and birthing ball education tended to have smoother labors compared to those who did not receive these interventions. It can be concluded that the integration of prenatal exercise and birthing ball education has been proven effective in improving the smoothness of labor. This intervention can be implemented as a safe and beneficial non-pharmacological alternative within maternity nursing care. It is hoped that healthcare practitioners can integrate this program into antenatal care to optimize maternal preparedness for labor.